PENGGUNAAN ALAT PERAGA UNTUK MENINGKATKAN PEMAHAMAN KONSEP ILMU PENGETAHUAN ALAM (IPA) SEKOLAH DASAR MATERI WUJUD ZAT PADAT DAN SIFTANYA - Gita Erlangga Kurniawan (Universitas Wiralodra, 2019)
This study describes the understanding of students in science learning about the form of objects and their properties using teaching aids. Subjects In this study were fourth grade students of SDN 2 Klayan Cirebon Regency which amounted to 47 students with details of the number of male students 27 and female 20. The research method used was classroom action research. The stages of the study consisted of (1) preparing a plan of action (planning), (2) implementing an action (acting), (3) observing (observing), and reflecting (reflecting). The results of the study showed that at the beginning of learning (prasiklus) only 17 students (36%) graduated and increased in the first cycle to 37 students (79%). While students who did not pass or get scores below the KKM in the pre cycle there were 30 (64%) students in the first cycle to 10 students (21%). The acquisition of the average value has increased, namely the average of 81 students in the first cycle and an increase of 23.44 from the initial data of students which is only 67.56. In the second cycle the average score of 92 students increased from the first cycle of only 81. In addition, the percentage of students who graduated experienced an increase from the first cycle of students who graduated 37 students (69%) in the second cycle 44 students (94%) graduated because there are only 3 students (6%) who have not graduated. Keywords: , ,